2019
DOI: 10.1001/jamasurg.2018.4647
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning in Older Adults With Multiple Chronic Conditions Undergoing High-Risk Surgery

Abstract: Conflict of Interest Disclosures: Dr Chu reported serving as the national proctor for novel surgical technique of trileaflet aortic valve neocuspidization using autologous pericardium (Ozaki procedure) for the Japanese Organization for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 6 publications
1
36
0
Order By: Relevance
“…This highlights a need for education and quality improvement, and holds health policy implications. 5 Despite patients and physicians recognizing the importance of ACP, patients with cancer frequently have no documented end-of-life plan. 6 Barriers to the documentation of ACP frequently include an absence of training and lack of sufficient time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights a need for education and quality improvement, and holds health policy implications. 5 Despite patients and physicians recognizing the importance of ACP, patients with cancer frequently have no documented end-of-life plan. 6 Barriers to the documentation of ACP frequently include an absence of training and lack of sufficient time.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights a need for education and quality improvement, and holds health policy implications. 5 …”
Section: Discussionmentioning
confidence: 99%
“…A research letter in JAMA Surgery explored a population of elderly patients with chronic comorbidities and found that only 30% of those who died within a year of surgery had any ACP documented. 8 Likewise, a review of ACP and end-of-life discussions in the perioperative period found that, although providers seemed to view these discussions positively, limited educational and training content was available. 9 Despite the limited evidence to this point regarding perioperative ACP, there are a few populations where this approach has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…"Data on the receipt of the aforementioned 6 LSTs [cardiopulmonary resuscitation, intensive care unit care, chest compression, intubation with mechanical ventilation, nasogastric tube feeding, and intravenous nutrition] in patients' last month of life were retrieved from medical records and supplemented by caregivers' reports during bereavement follow-ups" [16]. This example specifies that the review was of care received in the last month of life, but studies relying on retrospective chart review did not consistently specify the window of treatment time considered.…”
Section: Methodsmentioning
confidence: 99%